Functional identification of a rare vascular endothelial growth factor a (VEGFA) variant associating with the nonsyndromic cleft lip with/without cleft palate. Issue 1 (1st January 2021) - Sun, Bohui; Liu, Yangjia; Huang, Wenbin; Zhang, Qian; Lin, Jiuxiang; Li, Weiran; Zhang, Jieni; Chen, Feng
ABSTRACT: Vascular endothelial growth factor A (VEGFA) is a crucial growth factor, which participates in multiple processes of human growth and development, such as angiogenesis and osteogenesis and is also necessary for development of palate. The purpose of this study was to investigate the effect of a rare VEGFA mutation (NM_001025366.2 773 T > C p.Val258Ala) on the cell functions and osteogenesis. Here, we found that the VEGFA mutation has adverse effects on the function of human embryonic palatal plate mesenchymal (HEPM) cells, and may affect the development of palate. The VEGFA mutation has adverse effects on promoting cell proliferation and migration and inhibiting apoptosis in HEPM and HEK–293 cells. In addition, the mutant VEGFA allele has a negative influence on osteogenesis. Taken together, the rare variant of the VEGFA gene had an adverse effect on cell functions and osteogenesis, which may impact the development of the palate. And these findings suggested that VEGFA mutation (c.773 T > C) may lead to nonsyndromic cleft lip with or without cleft palate and also provide a new insight into the mechanism of VEGFA gene in osteogenesis and palatogenesis. GRAPHICAL ABSTRACT: uf0001